2021
DOI: 10.3390/jcm10153393
|View full text |Cite
|
Sign up to set email alerts
|

Neurally-Adjusted Ventilatory Assist (NAVA) versus Pneumatically Synchronized Ventilation Modes in Children Admitted to PICU

Abstract: Traditionally, invasively ventilated children in the paediatric intensive care unit (PICU) are weaned using pneumatically-triggered ventilation modes with a fixed level of assist. The best weaning mode is currently not known. Neurally adjusted ventilatory assist (NAVA), a newer weaning mode, uses the electrical activity of the diaphragm (Edi) to synchronise ventilator support proportionally to the patient’s respiratory drive. We aimed to perform a systematic literature review to assess the effect of NAVA on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We have not assessed sensitivity and specificity of other extubation readiness scores ( 20), yet, every effort should be made to introduce effective MV strategies. Neurally adjusted ventilatory assist (NANA) might prove helpful in gradual weaning of patients with a well-trained respiratory therapist (21).…”
Section: Discussionmentioning
confidence: 99%
“…We have not assessed sensitivity and specificity of other extubation readiness scores ( 20), yet, every effort should be made to introduce effective MV strategies. Neurally adjusted ventilatory assist (NANA) might prove helpful in gradual weaning of patients with a well-trained respiratory therapist (21).…”
Section: Discussionmentioning
confidence: 99%
“…There are also novel modes of conventional ventilation utilizing triggers other than volume, pressure, or flow which are the standard triggers for ventilator breaths NAVA uses EAdi signal to trigger inspiration; this mode has been shown to improve the patient‐ventilator synchrony and mitigate the risk of ventilator over assistance when compared with pressure support ventilation 3,8 . Pediatric studies have shown that the use of NAVA significantly reduced the duration of mechanical ventilation, length of stay, and sedative requirement in children with lung disease; however, more studies are needed to more completely assess the effect of NAVA on clinical outcomes and treatment costs in ventilated children 10 …”
Section: Conventional Mechanical Ventilationmentioning
confidence: 99%
“…There are also novel modes of conventional ventilation utilizing triggers other than volume, pressure, or flow which are the standard triggers for ventilator breaths NAVA uses EAdi signal to trigger inspiration; this mode has been shown to improve the patient-ventilator synchrony and mitigate the risk of ventilator over assistance when compared with pressure support ventilation 3,8. Pediatric studies have shown that the use of NAVA significantly reduced the duration of mechanical ventilation, length of stay, and sedative requirement in children with lung disease; however, more studies are needed to more completely assess the effect of NAVA on clinical outcomes and treatment costs in ventilated children 10. 4 | NON CONVENTIONAL MECHANIC AL VENTIL ATI ON (HFOV, HJ V, HFPV, AND A PRV )When conventional ventilation fails to resolve issues of oxygenation and ventilation in severe lung disease, then nonconventional TA B L E 4 Recommended settings for conventional mechanical ventilation historically been applied in the neonatal and pediatric population 11.…”
mentioning
confidence: 99%